From theory to practice: A case study on estimating the costs of improving animal welfare on Simmental alpine dairy farms - Agung Triatmojo; Zazie von Davier; Greta Fichter; Matthias Gauly; Thomas Zanon (PLoS ONE, 2026)
This case study estimates the economic implications of enhancing animal welfare (AW) in Alpine dairy farming, specifically focusing on Simmental cattle in both conventional (CON) and organic (ORG) farms. Given the increasing demand for higher welfare standards from consumers and policymakers, it is important to assess the economic feasibility of implementing these practices. The primary aim of this study is to develop a proof of concept for estimating the costs involved in meeting specific AW standards. Data were collected from 30 dairy farms (15 CON and 15 ORG), and AW scores were evaluated using both resource-based and animal-based indicators (total score of 90 points). Additionally, AW costs were assessed by calculating the cumulative additional costs, offset by potential benefits. Results show ORG farms achieve higher AW scores (73.99) compared to CON farms (70.28) but incur significantly higher production costs (€1.263/kg ECM for ORG vs. €0.977/kg ECM for CON), primarily due to the dilution effect caused by lower milk production on ORG farms. A nonlinear relationship between AW scores and AW costs was also observed, indicating that higher AW scores in initial farm conditions could, in some cases, lead to cost savings, particularly in larger and more efficient farms. The study emphasizes the need for clearly defined AW standards and a corresponding scoring system that reflects both the welfare impacts on animals and the economic feasibility for farmers. Further, we argue that the aggregation of AW scores should not merely categorize welfare on a simple best-to-worst continuum. Rather, it should account for the specific targets and conditions that policymakers and consumers are willing to support financially.